Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1074/jbc.m809064200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Deficiency Causes a Complex Phenotype because of Hepatic SREBP/Insig Dysregulation Associated with Endoplasmic Reticulum Stress

Abstract: Regulation of hepatic cholesterol biosynthesis, lipogenesis, and insulin signaling intersect at the transcriptional level by control of SREBP and Insig genes. We previously demonstrated that peroxisome-deficient PEX2 ؊/؊ mice activate SREBP-2 pathways but are unable to maintain normal cholesterol homeostasis. In this study, we demonstrate that oral bile acid treatment normalized hepatic and plasma cholesterol levels and hepatic cholesterol synthesis in early postnatal PEX2 mutants, but SREBP-2 and its target g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 64 publications
(84 reference statements)
9
56
3
Order By: Relevance
“…Similar to the few observations in patients with PBD, generalized and conditional mouse models lacking PEX5 or PEX2 in hepatocytes exhibit mitochondrial and ER alterations and lipid accumulations [16,21,80]. These changes closely follow the loss of functional peroxisomes in time, illustrating the dependence of other cellular compartments on intact peroxisomes [81,82].…”
Section: Mitochondrial Anomalies In Murine Hepatocytes Lacking Functisupporting
confidence: 56%
See 1 more Smart Citation
“…Similar to the few observations in patients with PBD, generalized and conditional mouse models lacking PEX5 or PEX2 in hepatocytes exhibit mitochondrial and ER alterations and lipid accumulations [16,21,80]. These changes closely follow the loss of functional peroxisomes in time, illustrating the dependence of other cellular compartments on intact peroxisomes [81,82].…”
Section: Mitochondrial Anomalies In Murine Hepatocytes Lacking Functisupporting
confidence: 56%
“…It was also shown that the ER compartment is enlarged in peroxisome deficient hepatocytes and mediators of ER stress signaling pathways (PERK, ATF4) are upregulated [80][81][82]. It was suggested that these ER perturbations deregulate SREBP signaling and cholesterol homeostasis [82].…”
Section: Other Cellular Adaptations In Murine Pex5 Deficient Hepatocytesmentioning
confidence: 98%
“…If the cell cannot achieve these goals autophagy and apoptosis are induced (Schroder and Kaufman, 2005). ER stress has been experimentally observed in a Pex2−/− mouse model for peroxisomal biogenesis disorders (PBD) supporting the protective function of plasmalogens in oxidative stress (Kovacs et al, 2009). Furthermore high levels of lysoplasmalogens inhibit NaK-ATPase (Schonefeld et al, 1996) and lack of plasmalogens may result in impaired Ca 2+ release, intracellular Ca 2+ overload and ER stress (Hale et al, 1998).…”
Section: Er-stress Reactionmentioning
confidence: 98%
“…As a consequence, Pex5 knockout mice lose body weight despite increased food intake. Disruption of peroxisome function, however, seems to compromise not only carbohydrate but also cholesterol metabolism, which is regulated by the sterol regulatory element-binding protein (SREBP) family of transcription factors (Kovacs et al 2004(Kovacs et al , 2009). Hepatocytes of peroxisome-deficient Pex2 -/-mice have been reported to experience ER stress, which in turn disturbs the expression of SREBP-2, SREBP-1c and Insig-2a, leading to further deregulation of endogenous sterol response pathways.…”
Section: Mysterious Functions: the Spectrum Of Peroxisomal Tasks Widensmentioning
confidence: 99%